Encapsulation of Nutraceutical Ingredients in Liposomes and Their Potential for Cancer Treatment. (17th November 2018) - Dutta, Sayantani; Moses, Jeyan Arthur; Anandharamakrishnan, C.
Abstract: At present, cancer is one of the major diseases in the world affecting numerous lives. There have been various approaches to combat the disease, particularly involving chemical interventions (chemotherapy). However, owing to serious side effects of chemotherapy, employment of natural supplements in cancer therapy has been long desired. Nutraceuticals are currently being studied as a medicament, to act as both preventive and curative measure. Nutraceuticals provide both nutrition and therapeutic benefits; besides, they are natural and biocompatible, and therefore pose no side effects. This facilitates their ready acceptance as dietary supplements with no requirements of special dosage and concerns over long-term usage. Nutraceuticals can be derived from the natural resources such as spices, fruits, vegetables, and plants. However, nutraceuticals are vulnerable to environmental stresses that necessitate encapsulation for long-term storage and required bioavailability. The review collates the findings on encapsulated nutraceuticals in liposomes for cancer therapy. The article provides a coherent overview of the research conducted on liposomal administration of nutraceuticals to target various forms of cancer, explaining the advances made.